Fitness Cost of Daptomycin-Resistant Staphylococcus aureus Obtained from in Vitro Daptomycin Selection Pressure - Li, Shuguang; Yin, Yuyao; Chen, Hongbin; Wang, Qi; Wang, Xiaojuan; Wang, Hui (Frontiers in Microbiology, 2017)
Daptomycin resistant Staphylococcus aureus strains are well documented, but have not been reported in China. To elucidate the evolution adaptability and fitness cost of daptomycin resistant S. aureus, three daptomycin susceptible strains, Pre3 (MRSA, ST239-t037), Pre5 (MRSA, ST239-t037), and Pre14b (MSSA, ST188-t189), were isolated from patients with bloodstream infections, and serially passaged in MH broth with a gradient of daptomycin concentration to select for resistance. Highly daptomycin resistant mutants were obtained after screening for 34 passages. The daptomycin MICs increased from 0.5 μg/ml in the parent strains to 16 μg/ml in the mutants, which remained tolerant to 4 μg/ml of daptomycin for more than 160 generations. The growth of the three mutant strains was slower than that of the parent strains, with relative fitness cost of 34.8%, 19.2% and 15.0%, respectively. The in vitro serum tolerance of the mutants was decreased, and the lethality and pathogenicity in mice was weakened (P <0.01). Transmission electron microscopy and flow cytometry found that the cell walls of the mutants were significantly thicker (from 38.6% to 75.4%) than those of the parent cells. Mutation L826F of mprF was found in Post14b, G299V and L473I of mprF and Y225N of walK were found in Post3, whilst T345A of mprF, S52N of graS and F473I of walK were found in Post5. Thus, stable daptomycin resistant mutants could be obtained from a middle-short term of in vitro daptomycin selection, and according to their fitness cost, some prevention and control work may be done to cope with daptomycin resistant S. aureus that may appear in China in the future.